Book Review of Art-Care Practices for Restoring the Communal: Education, Co-inquiry, and Healing - Fidyk, Alexandra (Art/Research International)

(untitled) (University of Alberta, 2024)
Barbara Bickel and R. Michael Fisher, through their co-creative life-partnership, have composed in their book Art-Care Practices for Restoring the Communal: Education, Co-inquiry, and Healing, a beneficial guide (project) for research, education, academe, and art. They provocatively decentre deep-rooted beliefs in individualism and competition—aspects that dominate today’s academic life, promotion, publishing quotas, and journal rankings. In their thoughtful tarrying, they offer the reader three equally important text sections: “Communidreaming on Theory”; “Spontaneous Creating on Practice”; and “Gestating on Service.” Opening this collective is a detailed glossary, followed by a foreword of poetry, psalm, and photographed process which introduces Bracha Ettinger and her guiding Matrixial theory. Thereafter, Bickel and Fisher’s story of inspiration transports us into their intimate and courageous practice of Spontaneous Creation-Making (SCM) with 35 co-creatives—“an invitational way to make and re-make sense of the troubling times” (p. xxxv) which unfolded during the pandemic and shutdown in North America.